Brain changes associated with language development and learning: A primer on methodology and applications. (April 2020) - Luk, Gigi; Pliatsikas, Christos; Rossi, Eleonora
Abstract: Brain plasticity associated with second language acquisition and learning has been a focus of research in the past two decades. Recent research on cognitive neuroscience has enriched current understanding on the neurological underpinning of second language learning. Beyond behavioral findings, examining brain functions and structures provides a biological explanation of how language acquisition (as a natural experience) and learning (as an active skill and knowledge acquisition process) shapes the human brain. Together, combining cognitive neuroscience methods and second language acquisition and learning has offered an opportunity for cross-disciplinary collaboration. To facilitate cross-disciplinary understanding and potential research collaboration, this review paper aims to provide an overview of the major cognitive neuroscience methodologies adopted to study second language acquisition and learning. A selection of empirical studies covers second language acquisition in developing children, bilingualism as a naturally-occurring experience, and short-term second language learning in laboratory settings. Brain structural (diffusion tensor imaging, DTI; and voxel-based morphometry, VBM) and functional (electroencephalography, EEG; and event-related potentials, EPRs) methods are briefly discussed with suggested further readings. The paper ends with future directions using these methodologies to explore brain changes in response to second language teaching and learning experience.